Islam, history, society, and civilization (New Jersey : A Film Media Group, 2004)
Covers past and present-day philosophies, practices, and events that define Islam. Encourages students to consider how different interpretations of religion can effect government, culture and individual lives.
Keywords: Civilization, Islamic; Islam -- History